PENGARUH KEDISIPLINAN DAN KEPUASAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA BIRO PENGADAAN BARANG DAN JASA SEKRETARIAT DAERAH PROVINSI PAPUA BARAT - Aries Tarkus Rumbewas; Manuel Lambi; Nikolina Balia (JURNAL LENTERA BISNIS, 2026)
Employee work effectiveness in government procurement units is a strategic issue in bureaucratic reform that demands deeper empirical investigation, particularly in eastern Indonesia. This study aims to analyze the partial and simultaneous effects of work discipline and job satisfaction on employee work effectiveness at the Procurement of Goods and Services Bureau (BPBJ) of the West Papua Provincial Regional Secretariat. Grounded in Gibson, Ivancevich, and Donnelly's (2019) work effectiveness theory, Hasibuan's (2019) work discipline theory, and Herzberg's (1966) two-factor theory alongside Robbins and Judge's (2019) job satisfaction theory, this research employs a quantitative descriptive-associative approach with multiple linear regression analysis. Data were collected from 62 civil servant respondents (46 PNS and 16 P3K) using purposive sampling through Likert-scale questionnaires. Results indicate that: (1) work discipline has a positive and significant effect on work effectiveness (β=0.451; t=5.132; sig=0.000); (2) job satisfaction has a positive and significant effect on work effectiveness (β=0.318; t=3.874; sig=0.000); (3) simultaneously both variables significantly affect work effectiveness (F=68.219; sig=0.000) with R²=0.694, meaning 69.4% of the variation in work effectiveness is explained by these variables. Work discipline is the more dominant predictor. This study underscores the importance of strengthening value-based discipline systems and improving job satisfaction through fair compensation and career development to enhance transparent and accountable procurement processes.